2016
DOI: 10.1137/15m1039857
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotically Compatible Fourier Spectral Approximations of Nonlocal Allen--Cahn Equations

Abstract: We study Fourier spectral approximations of a nonlocal Allen-Cahn (NAC) equation that reduces to the conventional Allen-Cahn equation in the local limit. We show that the Fourier spectral methods are asymptotically compatible in the sense that they provide convergent approximations to both nonlocal and local models. Furthermore, we provide various error estimates. In particular, it is shown that the numerical solutions of nonlocal models converge to those of the corresponding local models uniformly at a rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 42 publications
2
57
0
Order By: Relevance
“…Stability tests. For the case ρ δ (|s|) ∈ L 1 (R 2 ), i.e., α ∈ [0, 2), it has been proved in[15] that the steady state solution u * to the NAC equation (1.1) is continuous if ε 2 C δ ≥ 1, where…”
mentioning
confidence: 99%
“…Stability tests. For the case ρ δ (|s|) ∈ L 1 (R 2 ), i.e., α ∈ [0, 2), it has been proved in[15] that the steady state solution u * to the NAC equation (1.1) is continuous if ε 2 C δ ≥ 1, where…”
mentioning
confidence: 99%
“…Such models have attracted the attention of community in recent years [8,239,327,405,408]. Algorithmic development and numerical analysis concerning these nonlocal models (including the fractional ones in either space or time or both ) can be found in [6,49,159,150,238,260,394,445]. Related algorithmic studies with respect to different applications were presented in [17].…”
Section: Fluid and Solid Mechanicsmentioning
confidence: 99%
“…For spatially nonlocal phase field models, due to the spread of nonlocal interactions, the phase field variables may no longer be as smooth as their local counterpart. They may also lead to narrower interfacial region and permit singularities across the interface or at the defects [159,239,394]. 7.5.2.…”
Section: Fluid and Solid Mechanicsmentioning
confidence: 99%
“…In the special case of periodic domains, the multipliers are in fact the eigenvalues of L δ,β (see Section 4.1). Eigenvalues of nonlocal Laplace operators have been recently studied in [12,13]. The work [12] focused on nonlocal eigenvalues and spectral approximations for a 1-D nonlocal Allen-Cahn (NAC) equation with periodic boundary conditions, and showed that these numerical methods are asymptotically compatible in the sense that they provide convergent approximations to both nonlocal and local NAC models.…”
Section: Introductionmentioning
confidence: 99%
“…The work [12] focused on nonlocal eigenvalues and spectral approximations for a 1-D nonlocal Allen-Cahn (NAC) equation with periodic boundary conditions, and showed that these numerical methods are asymptotically compatible in the sense that they provide convergent approximations to both nonlocal and local NAC models. The work [12] provides numerical examples corresponding to specific integral kernels for which the eigenvalues are computed explicitly. A more general method is provided in [13] for the accurate computations of the eigenvalues in 1, 2, and 3 dimensions for a class of radially symmetric kernels.…”
Section: Introductionmentioning
confidence: 99%